Phản ứng của giá cổ phiếu đối với biến động chính sách kinh tế thế giới và chính sách tiền tệ tại Việt Nam - Lê Hồ An, Châu; Ngô Sỹ, Nam; Nguyễn Thị Mai, Huyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This paper makes an empirical analysis of stock index in response to the global economic policy uncertainty and monetary policy shocks in Vietnam. Applying Structural Vector Autoregressive Model (SVAR) imposed by short-run restrictions, and the monthly data from 2008:M1 to 2017:M12, we find an immediate response of VN-Index to the adjustment in global economic policies, indicating that an increase in Economic policy uncertainty leads to a deep fall in stock prices which may arise due to the changes in investors' sentiments and monetary policy intervention of the State Bank of Vietnam. Research results show that expansionary monetary policy represented by the increase in money supply and exchange rate raises stock prices while its response to short-term interest rate changes is statistically insignificant. Moreover, the findings also reveal that oil price shock leads to a temporary decrease in stock price
Keywords: Stock price; Economic policy uncertainty; Monetary policy; Stock market; SVAR; Vietnam